Changes in the ocular surface and tear film during 30 days of daily use of hydrogel and silicone hydrogel soft contact lens - Dávila, Juanita (Universidad de La Salle. Revistas. Ciencia y Tecnología para la Salud Visual y Ocular., 2012)
Morphological and physiological changes induced by contact lens (CL) are mainly due to hypoxia, mechanical trauma and toxicity associated with time of use of CL. Objective: To determine changes in the ocular surface and tear film during 30 days of daily use of hydrogel and silicone hydrogel CL. Materials and methods: 20 individuals, novices in the use of CL signed an informed consent and were adapted with Lotrafilcon A and Vasurfilcon A. Conjunctival hyperemia, Schirmer I, TBUT, corneal staining and comfort were assessed before adaptation and during each check-up (4 and 8 hours, day 3, 7, 11, 15, 19, 23, 27 and 30). The Wilcoxon rank test (IC 95 %), the Mann/Whitney test (IC 95 %) and the Spearman correlation were used. Results: Alterations were evident in all tests studied after 4 hours of use of the two lenses. The greatest decrease (p < 0.05) in the tear film quality was on day 3 of use of Lotrafilcon A and Vasurfilcon A (4.5 s and 5.5 s, respectively) and in the quantity of the tear film was on day 30 (12 min/5 min and 9 min/5 min, respectively). There was a gradual increase in the percentage of patients with corneal staining and with conjunctival hyperemia during the 30 days. There were no statistical differences (p > 0.05) or clinically significant differences between the two groups of lenses. Conclusions: Soft CL with high and low Dk/t during 30 days of daily use cause significant changes in the ocular surface and tear film, without showing any differences among the changes generated by the two types of lenses.